Nepremoženjska škoda zaradi izgube počitnic - Možina, Damjan (Podjetje in delo, 2014)
The article presents the judgment of ECJ in the case Leitner (C-168/00) which acknowledged non-material damages resulting from breach of package holiday contract. It describes the effects of the judgment in Austrian law and refers to the recognition of loss of enjoyment of holidays in other European countries. Recently, the High court of Maribor has decided a similar case, but has rejected the claim on the grounds that the Slovenian Code of Obligations doesn't recognize such loss and that interpretation in accordance with EU law is not possible. The author disagrees with this viewpoint and claims that there is no numerus clausus of cases where monetary compensation of non-material loss is recognized in Slovenian law. Interpretation in accordance with EU law is possible and would be a far better solution with regard to the judgment than the alternatives. Based on Code of Obligations and the Directive, such loss could be recognized as mental suffering due to diminishment of life activities or due to infringement of personality rights.
Keywords: kršenje; nepremoženjska škoda; odškodnina; odškodninska odgovornost; pogodbe; sodna praksa; turistične agencije